Aristotelismus und Averroismus in der politischen Theorie bei Marsilius von Padua und Wilhelm von Ockham - Miethke, Jürgen (Revista portuguesa de filosofia, 2019)
The paper is aiming to look at the importance of the Arabian political philosopher Averroes (Ibn Rušd) for the reception of the political philosophy of the Greek philosopher Aristotle in the Latin West by analyzing the exemple of two maior medieval authors (Marsiglio of Padua and William Ockham) for “averroistic” doctrines, in order to check the often discussed so called “Political Averroism” in the medieval Latin political philosophy. As result there seems to emerge the insight, that “Political Averroism” is only a “historiographical myth”, for Marsiglio is showing only some minor points of reference to averroistic topics, whereas Ockham seems free of clear relationship to “Averroism”.